Morphological and molecular characterisation of Aporcelaimellus nigeriensis sp. n. (Dorylaimida: Aporcelaimidae), a remarkable dorylaim from Nigeria - Rashidifard, M.; Bello, T.T.; Fourie, H.; Coyne, D.; Peña-Santiago, R. (Brill, 2020)
A new species of Aporcelaimellus, collected in a watermelon field in Nigeria, is described, including its morphological and molecular (D2-D3 28S-rDNA, 18r-DNA) characterisation. Aporcelaimellus nigeriensis sp. n. is distinguishable by its 2.76-3.55 mm length, very coarse ventral body pores, lip region offset by deep constriction and 24-27 μm broad odontostyle 30-36 μm long at its dorsal and 28-31 μm at its ventral side, neck 648-779 μm long, pharyngeal expansion occupying 54-60% of total neck length, uterus 300-473 μm or 2.1-3.2 body diam. long and tripartite, V = 49-54, tail short and convex conoid (27-41 μm, c = 72-115, c′ = 0.5-0.7), spicules 108-137 μm long, and 9-10 spaced ventromedian supplements with hiatus. LSU analysis revealed a close relationship of A. nigeriensis sp. n. with other Aporcelaimellus species and questioned, once more, the monophyly of Aporcelaimidae. SSU phylogenetic tree was not able to resolve the relationship between the new species and other closely related species.